Negative manifestations on occasion of joys and their impact on Saudi society: A study applied to Afif governorate - Al-Otaibi, Talal Fahd Munir (Journal of Humanities & Social Sciences, 2023)
The study aimed to identify some negative behavioral manifestations in people accompanying joys in Afif governorate. The study used the analytical descriptive curriculum. The researcher selected him for a sample (150); Data were collected through the questionnaire, using a statistical analysis method. The study found negative manifestations practised by young people in joys. and the appearance of some ethical behavioural irregularities, with many violations of traffic regulations and public taste in society and found some suggestions and solutions, namely the need to work hard on regulations and laws governing celebrations of joy, with the need to increase the number of security personnel and to use citizens’ volunteers in organizing, To preserve public taste, activate the role of the Authority of Order of Favor and Disregard of Denial.